STRATEGI ADAPTASI PENDUDUK DESA GURUKINAYAN PASCA ERUPSI GUNUNG SINABUNG - Syapitri, Henny; Hutajulu, Johansen (Jurnal Ilmiah Keperawatan, 2018)
The occurrence of the Sinabung eruption resulted in damage to houses and land, even some residents had to lose their homes due to heavy damage and were not fit to be occupied. This makes people very sad, feeling confused, anxious because the eruption still continues. Even so, this does not discourage people from staying in Gurukinayan Village. This high fighting spirit makes people able to survive even not wanting to move house. They tried to make adjustments after natural disasters, in order to survive. Adaptation by the community aims to enable them to re-adapt adaptively. The purpose of this study was to analyze the adaptation strategies of Gurukinayan Village residents after the eruption of Mount Sinabung. This type of research is qualitative with a descriptive phenomenological approach. Data collection was done through participant observation and in-depth interviews with key informants who were victims of Mount Sinabung eruption. The analysis was carried out using a description of content analysis and life history with the number of participants 6. The results obtained were survival strategies conducted by Gurukinayan Village residents: On the health aspect: participants stated that they went to health services for treatment when experiencing health problems such as coughing, shortness of breath, flu, and fever, but there were some participants who made their own efforts by concocting traditional medicine, but there were also those who let the complaint heal themselves without having to go for treatment. In the psychological aspect: participants revealed a lot of the losses suffered due to eruptions, of course this made people experience deep sadness, but they still tried to stay motivated despite the many impacts experienced, this high enthusiasm made citizens become motivated to maintain their survival. Socio-economic aspects: Participants express the strong attachment and social interaction of citizens so that this is what makes citizens stay afloat. Infrastructure Aspect: participants said they were trying to improve infrastructure such as repairing damaged houses and land.